EDUCAÇÃO PERMANENTE: OSTEOPOROSE UMA CONVERSA COM OS PROFISSIONAIS DE SAÚDE - Bonacina, Daiane M.; Morlin, Cristiane B.; Begnini, Danusa; Paludo, Queli; Silva, Luiz A. A. d.; Tambara, Tiane T. (Salão do Conhecimento, 2013)
Resumo